Judicature - Wolfgang Heinz (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
The central issues that should be answered by the criminal statistic system pertain to the extent, structure and development of crime rates, the decisions of authorities for prosecution and sanctioning, the amount and type of imposed criminal sanctions, the enforcement of sanctions and the amount of reconviction after sanctioning. In this respect the German criminal statistic system has many deficits. Therefore it is necessary to supplement the existing statistics through periodical crime and victimisation surveys, to supplement the prison statistics and to implement statistics regarding suspected persons in the preliminary proceedings of public prosecutors, the enforcement of criminal sanctions as well as periodic reconviction statistic. But a comprehensive optimisation of the criminal statistics system requires the establishment of a statistical data base in which all data of the police crime statistics and all criminological relevant judicial decisions are recorded with pseudonymised individual data and subsequently linked with each other. This statistical data base will solve the problems of the current German crime statistics and will offer a basis for the implementation of new regular federal statistics, in particular with regard to the execution of a sentence and recidivism as well as the implementation of case-flow statistics and cohort studies.
Keywords: 330; case-flow statistics; cohort studies; conviction statistics; crime; sanctions; criminal; police crime statistics; prison statistics; probation service statistics; recidivism; reconviction statistic; statistics of criminal courts; statistics of the public prosecution offices; victimisation survey